PENGAMANAN DATA EKSTENSI FILE PDF DENGAN ALGORITMA AES DAN OTP - Musa Asyari Hidayat Jati; Yulison Herry Chrisnanto; Gunawan Abdillah (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The rapid development of technology presents new challenges in maintaining data security and privacy, especially concerning the security and confidentiality of documents that are vulnerable to eavesdropping and theft. Cryptography is the art and science of maintaining the confidentiality of messages using mathematical techniques related to data security, such as privacy, data integrity, and authentication. Cryptography can be applied in various sectors to enhance data security and protect sensitive information from risks such as unauthorized access, theft, and misuse of personal data. For instance, PDFs, which are digital document formats, are often used for various purposes, such as online applications, registrations, and digital transactions. AES (Advanced Encryption Standard) is a widely used encryption algorithm for protecting data, and the use of OTP (One Time Password) is a security technique that requires two different steps of verification to access a system. The AES algorithm provides strong security by utilizing complex transformations that make it very difficult to break, and the addition of OTP further enhances data security before it is returned to its original form.